'I opened the door to develop kuduro at JUPSON:' Music Studios as Spaces of Collective Creativity in the Context of Electronic Dance Music in Angola. Issue 6 (1st November 2020) - Alisch, Stefanie
Abstract : In this paper, I demonstrate how studios producing the Angolan electronic dance music (EDM) kuduro ('hard arse') in the capital Luanda are usefully investigated as social spaces of collective creativity. I triangulate interviews, observations, close listening and ethnographic participation. Researchers often portray kuduro and other EDM styles in the Global South using what I name the 'scarcity-resilience narrative'. This narrative gives short shrift to the rich cultural resources that feed into EDM styles. It perpetuates problematic stereotypes about African people and occludes the deliberate labour that kuduro practitioners ('kuduristas') invest in their craft. As kuduristas routinely affirm that sociability drives their interpersonal creative processes I portray kuduro studios as social spaces and construe kuduro's collective creativity through Extended Mind Theory (EMT). In my analysis, I first introduce kuduro studios in Luanda broadly and then focus on two influential kuduro studios: JUPSON and Guetto Produções. I show how kuduristas mobilise their collective creativity inside the studio by tapping into aesthetic strategies and conventions of the rich popular culture that surrounds them. Via EMT, I portray aesthetic duelling, puto-kota ('elder-younger') relationships, call-and-response and urban vocal strategies as collectively maintained social institutions. Inside the studio, kuduristas translate these rich resources into the sonic materiality of kuduro tracks which, in turn, are designed to achieve maximum audience response through mobilising the social institutions when radiating out into the world. This paper provides the first, fine-grained study of kuduro studios in Luanda. It de-centres the 'scarcity-resilience narrative' of Global South EDM by focusing on collective creativity and, as such, offers a fresh epistemological position on the study of music studios, Global South EDM and popular music in Angola.